Taxa de ingesta oral em pacientes hospitalizados com disfagia durante a pandemia COVID-19 - Felippe, Bianca de Souza (Universidade Federal de São Carlos, 2022)
Purpose: to analyze the oral intake rate of patients with dysphagia hospitalized to a public hospital in Campinas-SP during the period of the COVID-19 pandemic. Method: Study of quantitative and retrospective methodology with document collection and analysis through indicators and records of hospital admissions, available in an electronic database, to analyze the oral intake rate of hospitalized patients with and without COVID-19 and with a diagnosis of dysphagia in the period between August 2020 and July 2021. Results: The study sample consisted of a database of 1013 hospital admissions, with 47.2% patients in the group with COVID-19 and 52.7% in the group without COVID-19. For the groups, the sample is characterized by males and both have an average age of over 60 years. For the group with COVID-19, a high risk of oral feeding was identified, since approximately 50% of patients receive an indication of an alternative feeding route in the first speech-language pathology evaluation, with a reduction to about 30% in the second evaluation. As for the group without COVID- 19, for the initial and final speech-language evaluation, approximately 70% of the patients present oral feeding conditions with the need for adjustments and compensations in the diet. Conclusion: Patients hospitalized with COVID-19 had a high incidence of oropharyngeal dysphagia. There was an evolution of food consistency in oral intake, for different levels of the FOIS scale, between the initial and final speech-language evaluation.
Oral intake rate in hospitalized patients with dysphagia during the COVID-19 pandemic
Keywords: Administração hospitalar; Fonoaudiologia; Infecções por coronavírus; Métodos de alimentação; Transtornos de deglutição; American speech-language-hearing association; Deglutition disorders; Feeding methods; Hospital administration; SARS-CoV-2 infection; CIENCIAS DA SAUDE::FONOAUDIOLOGIA; CIENCIAS DA SAUDE